Stochastic Calculus for Fractional Brownian Motion and Applications - Zhang, T. (Springer, 2017)
Fractional Brownian motion (fBm) has been widely used to model a number of phenomena in diverse fields from biology to finance. This huge range of potential applications makes fBm an interesting object of study.